First record of the Clam Shrimp Leptestheria venezuelica Daday, 1923 (Crustacea: Brachiopoda: Spinicaudata) from the North of Colombia - Oliveros-Villanueva, Jorge (2021)
Large branchiopods has been distributed in temporary waters around the world, but the knowledge about these organisms in Colombia is poorly known, especially leptesteriids, we report a new record of the Clam Shrimp Leptestheria venezuelica Daday, 1923 from the north of Colombia.